Influencing Factors of University Core Competence: An Empirical Study Based on the Entropy Weight Gray Relation Model - Yongqing Shi; Xiaojiang Yang (Discrete Dynamics in Nature and Society)
To measure the gray relation between the core competence of research universities and its influencing factors, this paper took the same period statistical data of the five research universities directly subordinate to the Ministry of Education of China as the research samples, all these five schools were shortlisted in the “World Top 300” rankings of USNews, QS, THE, and ARWU from 2014 to 2018, and the indicator systems of the four authoritative lists were taken as the basis; 30 representative indicators affecting the core competence of research universities were selected, and the gray relation model was adopted for the research; moreover, this paper applied the information entropy method to calculate the weight of each indicator and estimate the comprehensive gray relation between the core competence of research universities and the entire factor system. This research gives the rankings of the influencing factors of the core competence of research universities, and there is a 0.8485 degree comprehensive gray relation between the influencing factors and the core competence of research universities, which has further clarified the future development direction of research universities.